(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study analyses the characteristics of PU/MWNT nanocomposite films. For this purpose, several kinds of PU/MWNT nanocomposite films were prepared with four kinds of MWNT, MWNT contents and two kinds of dispersion times. ESD (Electrostatic Dissipation) films composed of polyurethane (PU) block copolymer and selected multi-walled carbon nanotube (MWNT) were also prepared by disperse processing with various MWNT contents and dispersion times. Its mechanical and chemical properties were investigated with respect to electrical conductivity. The tensile properties and chemical properties of PU/MWNT nanocomposite films were measured using UV-visible spectrometer. These properties were also discussed according to the manufacturing conditions of nanocomposite films. Furthermore, PU/MWNT films were made by dispersing them in five kinds of CNT contents and six kinds of dispersion times under the DMF (dimethylformamide) solution. The mechanical properties of the PU/MWNT films were analyzed by Instron and discussed for various dispersion conditions.